Bank financial performance: A comparison between Jamuna Bank & Southeast Bank Ltd - Rahman, S.M. Mahfuzur (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.